AN ANALYSIS OF POLITENESS MAXIMS USED BY THE HOST OF BUKAN EMPAT MATA TALK SHOW IN SEMANGAT GARUDA MUDA EPISODE - TAMALIA, JAN ADIEL (Jurnal Ilmiah Mahasiswa FIB, 2013)
Talkshow is a television program in which two or more people discuss various topics happening in society. In Indonesia, Bukan Empat Mata is one of talkshow programs that gains high rating with comedic bent brought by the host. In interacting with the guests, the host has to show politeness to give respect to others. Considering this is a humor talkshow, there is possibility to be impolite  hown by the host. This study aims at finding out the politeness maxims and the violated politeness maxims used by the host of Bukan Empat Mata.     This study is classified as qualitative research. The data of this study were the transciption of the host’s utterances in Garuda Muda episode which contained the politeness maxims and which violated the politeness maxims. In the data analysis, the writer classified the data in the form of table and gave further explanation according to the six politeness maxims.     The results of this study show that the host of Bukan Empat Mata talkshow applies all of the six politeness maxims. There are five utterances containing tact maxim, one utterance containing generosity maxim, eighteen utterances and many adjectival phrases containing approbation maxim, two utterances containing modesty maxim, seven utterances containing agreement maxim, and four utterances containing sympathy maxim. There are also violation of politeness maxims, which are thirteen utterances violating approbation maxims and two utterances violating modesty maxims.     The conclusion of this study shows that approbation maxim and agreement maxim are the most important maxims for the hosts of Bukan Empat Mata talk show to show politeness and respect to the guests by maximizing praise and agreement to the guests. However, the violation of the politeness maxims occurs for the sake of inviting laughter of the guests and audiences. The researcher of this study suggests further researchers to observe politeness study in different objects and occasions.  Keywords: politeness maxims, violated politeness maxims, talk show, Bukan Empat Mata